Pemanfaatan Sistem Embung Sebagai Sumber Air dan Pangan Keluarga di Desa Cikalong Tasikmalaya Jawa Barat - Kristiyanto Kristiyanto; Silvia Septhiani; Ihwan Zulkarnain (Prima: Journal of Community Empowering and Services, 2021)
Utilizing the Pond as A Water and Food Source in Cikalong Village Tasikmalaya West Java. Cikalong Village is administratively in the Tasikmalaya Regency, West Java, often experiencing drought every year, chiefly in the dry season, when the local people have difficulty obtaining water to meet their daily needs. The method used in the activity was a direct observation, interviews, and FGD (Focus Group Discussion). The number of people involved is 10-15 people, in which there are community leaders and farmers. This activity aims to determine the contribution and benefits of the pond, especially in the dry season which is prone to drought. Ponds can be an alternative solution, apart from being a water source, their function can also be developed for fish cultivation with an aquaculture system and vegetables with an aqua-plants system. Both systems are able to meet food needs on a family scale well, with the integration of various types of fish such as Cyprinus carpio, Oreochromis mossambicus and vegetables such as chili, leeks, tomatoes. The results of the activity showed that the benefits of making ponds around the house with sizes of 10x10 m, 5x5 m, and 3x3 m and in gardens with sizes 10x20 m to 20x20 are as water storage, fish cultivation and plant cultivation. The pond was a form of adaptation and mitigation of local communities in responding to the effects of drought properly. The Cikalong Village community can be categorized as a community that has a fairly high sensitivity to the surrounding environmental conditions in recognizing and mitigating drought problems.